Structural and optical properties of low temperature grown single crystalline GaN nanorods on flexible tungsten foil using laser molecular beam epitaxy. (19th June 2019) - Ramesh, Ch; Tyagi, P; Mauraya, A K; Senthil Kumar, M; Kushvaha, S S
Abstract: The single crystalline GaN nanorods (NRs) have been grown on flexible tungsten (W) foil using laser molecular beam epitaxy (LMBE) at low growth temperature of 600 °C. The field emission scanning electron microscopy showed the growth of GaN NRs having length, width and density of 400∼530 nm, 40–70 nm and 3.4 × 10 9 cm −2, respectively. The high-resolution transmission electron microscopy reveals the c -axis oriented growth of single crystalline GaN NRs on W foil. The photoluminescence spectroscopy shows that the GaN NRs possesses a strong near band edge luminescence at 3.41 eV with a line-width of ∼100 meV at room temperature which resembles the high optical quality of GaN nanorods grown on W foil. The possible mechanism of GaN nanords growth on W foil has been also discussed. The low temperature LMBE growth of single crystalline GaN NRs on flexible metal foil with high optical quality paves the way for the development of III-nitride based flexible opto-electronics devices.